2021
DOI: 10.1186/s12348-021-00258-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined endophthalmitis and orbital cellulitis in patients with corona virus disease (COVID-19)

Abstract: Purpose To document the presentation of unilateral combined endophthalmitis and orbital cellulitis in patients with COVID-19 infection and study their prognosis. Patients and methods This interventional case series study included 9 patients referred to the Ophthalmology Department, Minia University Hospital with unilateral combined endophthalmitis and orbital cellulitis between April 2020 and March 2021. In addition to the COVID-19 work-up, all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Of these, only one patient had paranasal sinusitis suggesting a distant source of infection in the rest. The authors suggested generalized poor immunity of patients, direct viral infection, and multisystem inflammatory syndrome related to COVID-19 as possible mechanisms of this unusual ophthalmic manifestation 160 …”
Section: Orbital Manifestations Of Coronavirus Disease 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, only one patient had paranasal sinusitis suggesting a distant source of infection in the rest. The authors suggested generalized poor immunity of patients, direct viral infection, and multisystem inflammatory syndrome related to COVID-19 as possible mechanisms of this unusual ophthalmic manifestation 160 …”
Section: Orbital Manifestations Of Coronavirus Disease 2019mentioning
confidence: 99%
“…Orbital apex syndrome is characterized by the involvement of the optic nerve and cranial nerves 3, 4, and 6 and the first division of the trigeminal nerve with painful visual loss, ophthalmoplegia, ptosis, proptosis, and loss of sensations 159 . Abdelkader et al 160 reported 9 cases of simultaneous unilateral endophthalmitis with orbital cellulitis as a presenting feature of COVID-19 infection. Of these, only one patient had paranasal sinusitis suggesting a distant source of infection in the rest.…”
Section: Orbital Manifestations Of Coronavirus Disease 2019mentioning
confidence: 99%
“…A few studies have also reported COVID-19-related orbital cellulitis and sinusitis [ 55 , 64 , 65 , 66 ]. It was shown that only 1 among 2742 patients in India presented orbital cellulitis secondary to pansinusitis [ 66 ].…”
Section: The Orbital Regionmentioning
confidence: 99%
“…22 Agarwal et al, 23 them, with 2 being culture negative. 23 Abdelkader et al 24 reported on 9 patients with simultaneous orbital cellulitis and endophthalmitis. Vitreous cultures had been negative, and the visual outcome was poor in those who survived.…”
Section: Endophthalmitis and Covid-19mentioning
confidence: 99%
“…Vitreous cultures had been negative, and the visual outcome was poor in those who survived. 24 Bilgic et al, 25 Stenotrophomonas maltofila. 25 All the patients had improved following PPV with intravitreal antibiotics 25 .…”
Section: Endophthalmitis and Covid-19mentioning
confidence: 99%